TRIP13 promotes metastasis of colorectal cancer regardless of p53 and microsatellite instability status. Issue 12 (28th October 2020) - Agarwal, Sumit; Behring, Michael; Kim, Hyung‐Gyoon; Chandrashekar, Darshan S.; Chakravarthi, Balabhadrapatruni V. S. K.; Gupta, Nirzari; Bajpai, Prachi; Elkholy, Amr; Al Diffalha, Sameer; Datta, Pran K.; Heslin, Martin J.; Varambally, Sooryanarayana; et al.
Abstract : Overexpression of TRIP13, a member of the AAA‐ATPase family, is linked with various cancers, but its role in metastasis is unknown in colorectal cancer (CRC). In the current study, we investigated the role TRIP13 in experimental metastasis and its involvement in regulation of WNT/β‐catenin and EGFR signaling pathways. Evaluation of formalin‐fixed paraffin‐embedded (FFPE) and frozen tissues of adenomas and CRCs, along with their corresponding normal samples, showed that TRIP13 was gradually increased in its phenotypic expression from adenoma to carcinoma and that its overexpression in CRCs was independent of patient's gender, age, race/ethnicity, pathologic stage, and p53 and microsatellite instability (MSI) status. Moreover, liver metastases of CRCs showed TRIP13 overexpression as compared to matched adjacent liver tissues, indicating the biological relevance of TRIP13 in CRC progression and metastasis. TRIP13 knockdown impeded colony formation, invasion, motility, and spheroid‐forming capacity of CRC cells irrespective of their p53 and MSI status. Furthermore, xenograft studies demonstrated high expression of TRIP13 contributed to tumor growth and metastasis. Depletion of TRIP13 in CRC cells decreased metastasis and it was independent of the p53 and MSI status. Furthermore, TRIP13 interacted with a tyrosine kinase, FGFR4; this interaction could be essential for activation of the EGFR‐AKT pathway. In addition, we demonstrated the involvement of TRIP13 in the Wnt signaling pathway and in the epithelial–mesenchymal transition. Cell‐based assays revealed that miR‐192 and PNPT1 regulate TRIP13 expression in CRC. Additionally, RNA sequencing of CRC cells with TRIP13 knockdown identified COL6A3, TREM2, SHC3, and KLK7 as downstream targets that may have functional relevance in TRIP13‐mediated tumor growth and metastasis. In summary, our results demonstrated that TRIP13 promotes tumor growth and metastasis regardless of p53 and MSI status, and indicated that it is a target for therapy of CRC. Abstract : This study demonstrates overexpression of TRIP13 in colorectal cancers is independent of patient's gender, age, race/ethnicity, pathologic stage (primary and liver metastatic lesions), and p53 and microsatellite instability status. Furthermore, it establishes role of TRIP13 in colorectal cancer metastasis and identifies COL6A3, TREM2, SHC3, and KLK7 as its downstream targets. Additionally, TRIP13 activates EGFR‐AKT pathway via its interaction with FGFR4.